The Analysis of Leadership and Safety Behavior towards Safety Culture through Safety Climate - Ahmad Taufiq; Nila Krisnawati Hidayat; Firdaus Basbeth (Budapest International Research and Critics University, 2022)
Safety culture is a core value that must be owned by the company. However, a systematic review of the factors that mediate the formation of a safety culture is rarely discussed. The purpose of this study is to investigate the relationship between leadership, safety behavior, and safety climate in the formation of a safety culture in the mining industry, especially in the heavy equipment sector. The type of research used is quantitative research through surveys using the mono method. The survey was conducted in a one-shot/crossectional manner at all levels of leaders consisting of Managers, Dept heads, Supervisors, Leaders, and OHS practitioners spread over 5 different areas. This study found that safety climate had the greatest influence factor in building a safety culture (36%), followed by leadership (35%) and safety behavior (29%). Moreover, the norm behavior group is the biggest contributor in building a safety culture in the mining industry. In conclusion, a systematic review study is expected to increase the level of safety culture, all stakeholders have a role in providing a better understanding of safety culture to reduce mining accidents in the future.